Free-Circulating Methylated DNA in Blood for Diagnosis, Staging, Prognosis, and Monitoring of Head and Neck Squamous Cell Carcinoma Patients: An Observational Prospective Cohort Study. (6th January 2020) - Schröck, Andreas; Leisse, Annette; de Vos, Luka; Gevensleben, Heidrun; Dröge, Freya; Franzen, Alina; Wachendörfer, Malin; Schröck, Friederike; Ellinger, Joerg; Teschke, Marcus; Wilhelm-Buchstab, Timo; Landsberg, Jennifer; et al.
Abstract: BACKGROUND: Circulating cell-free DNA methylation testing in blood has recently received regulatory approval for screening of colorectal cancer. Its application in other clinical settings, including staging, prognosis, prediction, and recurrence monitoring is highly promising, and of particular interest in head and neck squamous cell carcinomas (HNSCCs) that represent a heterogeneous group of cancers with unsatisfactory treatment guidelines. METHODS: Short stature homeobox 2 ( SHOX2 ) and septin 9 ( SEPT9 ) DNA methylation in plasma from 649 prospectively enrolled patients (training study: 284 HNSCC/122 control patients; testing study: 141 HNSCC/102 control patients) was quantified before treatment and longitudinally during surveillance. RESULTS: In the training study, 59% of HNSCC patients were methylation-positive at 96% specificity. Methylation levels correlated with tumor and nodal category ( P < 0.001). Initially increased methylation levels were associated with a higher risk of death [ SEPT9 : hazard ratio (HR) = 5.27, P = 0.001; SHOX2 : HR = 2.32, P = 0.024]. Disease recurrence/metastases were detected in 47% of patients up to 377 days earlier compared to current clinical practice. The onset of second cancers was detected up to 343 days earlier. In the testing study, sensitivity (52%), specificity (95%), prediction of overall survival ( SEPT9 : HR = 2.78, P = 0.022; SHOX2 : HR = 2.50, P = 0.026), and correlation with tumor and nodal category ( P <0.001) were successfully validated. CONCLUSIONS: Methylation testing in plasma is a powerful diagnostic tool for molecular disease staging, risk stratification, and disease monitoring. Patients with initially high biomarker levels might benefit from intensified treatment and posttherapeutic surveillance. The early detection of a recurrent/metastatic disease or a second malignancy could lead to an earlier consecutive treatment, thereby improving patients' outcomes.